Therapy Dogs District-Wide: Mental Health and Well-Being Influences in PK-12 Education - Kathleen M. Farrand; Jae Young Jung (Education Sciences)
The mental health of prekindergarten (PK)-12th grade students is of extreme importance. Therapy dogs are a unique intervention to address mental health needs in educational frameworks. The purpose of this pilot study is to examine the components of a PK-12 district-wide therapy dog program and the implications for the mental health and well-being of students, faculty, and staff. This research used qualitative methods for semi-structured interviews with therapy dog handlers, observations including photographs, and researcher field notes of therapy dogs and handlers in their education environment. Thematic analysis of transcripts from semi-structured interviews was used for qualitative analysis. The results indicated that the strategic implementation of a district-wide therapy program supported a sustainable program that is integrated into the educational ecosystem. The participants perceived that the therapy dogs impacted mental health in the domains of social, emotional, and behavioral support. A district-wide systematic approach to addressing mental health and well-being needs of students, faculty, and staff with therapy dogs’ hinges on a comprehensive training and evaluation process, district-level support, and consistent implementation across educational settings. Therapy dogs can be embedded within educational structures to create a multilevel impact from the classroom to school to district level for a sustainable program. Therapy dogs positively contribute to the mental health and well-being of students, faculty, and staff in PK-12 education settings.